Killing Desire in Ensayo de un crimen [The Criminal Life of Archibaldo de la Cruz] (2021)
Ensayo de un crimen [The Criminal Life of Archibaldo de la Cruz ] is an adaptation by Luis Buñuelof the novel with the same title by Rodolfo Usigli. The main of this paper is to examine how narrativestrategies move from the novel to the film. The methodology is developed by means of the chronotopesestablished by M.M. Bakhtin, and also it is organized due the categorization of order, duration, andfrequency by Gerard Genette. The result of this study shows that the criminal desire comes from maincharacters’ Oedipal complex. NEvertheless, in the novel it is observed that criminal desire is also arisingfrom social disputes